Tumor Immune Microenvironment and Genetic Alterations in Mesothelioma - Hiltbrunner, Stefanie; Mannarino, Laura; Kirschner, Michaela B.; Opitz, Isabelle; Rigutto, Angelica; Laure, Alexander; Lia, Michela; Nozza, Paolo; Maconi, Antonio; Marchini, Sergio; D’Incalci, Maurizio; Curioni-Fontecedro, Alessandra; et al. (Frontiers in Oncology, 2021)
Malignant pleural mesothelioma (MPM) is a rare and fatal disease of the pleural lining. Up to 80% of the MPM cases are linked to asbestos exposure. Even though its use has been banned in the industrialized countries, the cases continue to increase. MPM is a lethal cancer, with very little survival improvements in the last years, mirroring very limited therapeutic advances. Platinum-based chemotherapy in combination with pemetrexed and surgery are the standard of care but prognosis is still unacceptably poor with median overall survival of approximately 12 months. The genomic landscape of MPM has been widely characterized showing a low mutational burden and the impairment of tumor suppressor genes. Among them, BAP1 and BLM present as a germline inactivation in a small subset of patients and increases predisposition to tumorigenesis. Other studies have demonstrated a high frequency of mutations in DNA repair genes. Many therapy approaches targeting these alterations have emerged and are under evaluation in the clinic. High-throughput technologies have allowed the detection of more complex molecular events, like chromotripsis and revealed different transcriptional programs for each histological subtype. Transcriptional analysis has also paved the way to the study of tumor-infiltrating cells, thus shedding lights on the crosstalk between tumor cells and the microenvironment. The tumor microenvironment of MPM is indeed crucial for the pathogenesis and outcome of this disease; it is characterized by an inflammatory response to asbestos exposure, involving a variety of chemokines and suppressive immune cells such as M2-like macrophages and regulatory T cells. Another important feature of MPM is the dysregulation of microRNA expression, being frequently linked to cancer development and drug resistance. This review will give a detailed overview of all the above mentioned features of MPM in order to improve the understanding of this disease and the development of new therapeutic strategies.